Spatial assessment of drought vulnerability using fuzzy-analytical hierarchical process: a case study at the Indian state of Odisha - Sunil Saha; Barnali Kundu; Gopal Chandra Paul; Kaustuv Mukherjee; Biswajeet Pradhan; Abhirup Dikshit; Khairul Nizam Abdul Maulud; Abdullah M. Alamri (Geomatics, Natural Hazards & Risk, 2021)
Droughts can be regarded as one of the most spatially complex geohazards, causing a severe impact on socio-economic aspects. Preparing a comprehensive drought management plan is necessary to mitigate drought risks, and the first step towards achieving it is the preparation of drought vulnerability map. The present study integrates geospatial methods with Fuzzy-Analytical Hierarchy Process (Fuzzy-AHP) technique, to prepare a drought vulnerability map for Odisha, India. Total of 24 parameters under 2 separate vulnerability categories, namely physical and socio-economic, was listed. Spatial layers were prepared for each parameter, and fuzzy membership approach was used to fuzzify each layer, and AHP was used to measure the weights of each parameter using pair-wise comparison matrices. Finally, drought vulnerability maps with five drought vulnerability classes (very-high, high, moderate, low, and very-low) were developed using weighted overlay method. The results show that 33.94% of the region falls under high-drought vulnerability category. Further, the approach was validated using statistical metrics, like area under the Receiver Operating Characteristics curves, Accuracy, Root-Mean-Square-Error and Mean-Absolute-Error. The results imply that the applied method is effective for determining drought vulnerability in the region, which would help the planners for formulating drought mitigation strategies.